Simulation and design of NSM strengthened beams using moment-rotation approach / Ahmad Azim Shukri - Ahmad Azim , Shukri (2019)
The near surface mounted (NSM) method is a technique for strengthening reinforced concrete (RC) beams which normally utilizes fibre reinforced polymer (FRP) bars or strips placed within grooves made on the soffit of the beams. One particular problem that has consistently been reported on the NSM method is the premature failure by concrete cover separation (CCS), which causes the beam to fail prior to the full potential of the strengthening reinforcement being utilized. Several methods have been proposed to determine the onset of CCS failure for NSM strengthened beams. The application of these methods however was found to be limited by the empirical formulations that were used, which severely affects their accuracy when applied to situations outside of the testing regime that formed the empirical formulations. In light of these problems, this research aims to present a method for the simulation and design of NSM strengthened beams that is less reliant on empirical formulations. To that end, the moment-rotation(M/?) approach was extended to allow for the simulation of NSM strengthened beams. The M/? approach applies the partial interaction theory which helps reduce the reliance on empirical formulations. The global energy balance approach (GEBA)was used in conjunction with the M/? approach to simulate CCS failure. The M/? approach was then applied to simulate and study the side-NSM (SNSM) method, which is an NSM-based strengthening method. The differences involved in simulating virgin and pre cracked SNSM strengthened beams was presented, where the former represents what is usually tested is laboratories and the latter is meant to simulate real world condition. The M/? approach was also applied to simulate the beams strengthened with hybrid method, which is another NSM-based method; furthermore, it was shown how the M/? approach can simulate intermediate crack (IC) de bonding through the use of single crack analysis. Lastly, a design procedure for the NSM method was proposed using closed form solutions derived from the M/? approach. The result of the research is as follows. The M/? approach for NSM strengthened beams was validated against published experimental results of RC beams strengthened with either of several types of NSM reinforcement, namely CFRP bars, CFRP strips, steel bars and GFRP bars. The validation process shows good correlation for the experimental and actual failure load. The M/? approach was also validated against experimental results of SNSM strengthened beams and hybrid strengthened beams, where good accuracy was also found. The final part of this research, the design procedure, was validated against published experimental results and achieves good accuracy. The results show that the M/? approach for NSM strengthened beams is able to simulate not only normal NSM method, but also other NSM-based methods; this versatility is a direct result of the reduced reliance on empirical formulations. Furthermore, the proposed design procedure gives the benefits of the M/? approach while also being simple enough for design engineers to use.